Meningkatkan Motivasi Belajar Siswa dengan Permainan 'Jelajahi Sekolahku' dalam Pembelajaran Pendidikan Pancasila - Rahmah Maulidi, Saniyatul Mafarrikhah; Pangestu, Widya Trio (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
The lack or decline of students' learning motivation requires highly engaging learning activities, one of which is by implementing learning innovations through games that can be used as learning media. This study aims to determine the effect of the